High‐Resolution Snowstorm Measurements and Retrievals Using Cross‐Platform Multi‐Frequency and Polarimetric Radars - Edwin L. Dunnavan; Jacob T. Carlin; David Schvartzman; Alexander V. Ryzhkov; Howard Bluestein; Samuel Emmerson; Greg M. McFarquhar; Gerald M. Heymsfield; John Yorks (Geophysical Research Letters, 2023)
Abstract Many studies have performed microphysical retrievals using radars of different frequencies, platforms, and methodologies. However, little is known about the consistency of retrievals derived from different radar platforms (i.e., airborne or spaceborne vs. ground‐based) and their methodologies. This study is the first to directly compare snow mass‐weighted mean diameter (Dm) retrievals from both nadir‐pointing airborne multi‐frequency radars and ground‐based polarimetric range‐height indicator radar scans along the same airborne flight track with a resolution of O(10m). Dm retrievals between each method produced mean absolute errors of 0.49, 0.74, and 0.93 mm where the largest differences were between the ground and aircraft retrievals. A triple‐frequency analysis suggests the possibility that snow aggregates were generally composed of needles. These results can be used as a benchmark for comparing retrieval methodologies and highlight the continued uncertainty regarding the optimal approach for ice microphysical retrievals.